Employment Trends of COVID-19 Graduates: The Case of a Malaysian Public University - Muhammad Iqmal Hisham Kamaruddin; Azuan Ahmad; Mohd Asri Husain; Saffa Nasuha Abd Hamid (Human Resource Management Academic Research Society, 2024)
Indexed by ERA